Particle swarm optimization approach for optimal distributed generation allocation in distribution system - L. Y., Wong; Siti Rafidah, Abdul Rahim; Mohd Herwan, Sulaiman; Omar, Aliman (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.